The mediating role of lung function on air pollution-induced cardiopulmonary mortality in elderly women: The SALIA cohort study with 22-year mortality follow-up - Dalecká, Andrea; Wigmann, Claudia; Kress, Sara; Altug, Hicran; Jiřík, Vítězslav; Heinrich, Joachim; Abramson, Michael J; Schikowski, Tamara (International journal of hygiene and environmental health, 2021)
BACKGROUND: Air pollution exposure is associated with reduced lung function and increased cardio-pulmonary mortality (CPM). OBJECTIVES: We analyzed the potential mediating effect of reduced lung function on the association between air pollution exposure and CPM. METHODS: We used data from the German SALIA cohort including 2527 elderly women (aged 51-56 years at baseline 1985-1994) with 22-year follow-up to CPM. Exposures to PM10, PM2.5, PM2.5 absorbance, NO2 and NOx were assessed by land-use regression modelling and back-extrapolated to estimate exposures at baseline. Lung function (FVC, FEV1) was measured by spirometry and transformed to GLI z-scores. Adjusted Cox proportional hazards and causal proportional hazards mediation analysis models were fitted. RESULTS: The survival analysis showed that reduced lung function (z-scores of FVC or FEV1 below 5% predicted) reflected significantly lower survival probability from CPM (p < 0.0001). Longterm exposures to NOx and NO2 were associated with increased risks of CPM (eg. HR = 1.215; 95%CI: 1.017-1.452 for IQR increase in NOx and HR = 1.209; 95%CI: 1.011-1.445 for IQR increase in NO2) after adjusting for reduced lung function and additional covariates. The associations of PM2.5 absorbance and CPM remained significant in models adjusted for FEV1/FVC, but the associations with PM10 and PM2.5 were not significant. The mediation analysis showed significant indirect effects of NO2 and NOx on CPM mediated through reduced FEV1 and FVC. The largest indirect effects were found for exposures to NO2 (HR = 1.037; 95%CI: 1.005-1.070) and NOx (HR = 1.028; 95%CI: 1.004-1.052) mediated through reduced FVC. The mediated proportion effect ranged from 13.9% to 19.6% in fully adjusted models. DISCUSSION: This study provides insights into the mechanism of reduced lung function in association between long-term air pollution exposure and CPM. The mediated effect was substantial for exposure to nitrogen oxides (NOx and NO2), but less pronounced for PM10 and PM2.5.
Keywords: pevné částice; Female; Lung; ženské pohlaví; znečištění ovzduší; lidé; Air Pollution; Particulate Matter; následné studie; kohortové studie; Cohort Studies; Follow-Up Studies; Air Pollutants; Aged; vystavení vlivu životního prostředí; plíce; senioři; látky znečišťující vzduch; Environmental Exposure; Humans